Adkar Change Management Model to Enhance the Use of LMS in Lectures: Does it Work? - M. Rezeki Muamar; Danny Meirawan; Munir; Endang Herawan; Rahmi Hayati (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
The ADKAR change management model was applied to enhance Learning Management System (LMS) adoption at higher education. This study highlights distinct differences between LMS users and non-users across all five stages of the ADKAR model Awareness, Desire, Knowledge, Ability, and Reinforcement. LMS users exhibited a higher level of Awareness, recognizing the rationale for LMS adoption and its benefits, while non-users showed limited understanding and engagement. In terms of Desire, LMS users demonstrated stronger motivation and a sense of urgency to adopt LMS, compared to non-users who lacked initiative and internal drive. Knowledge gaps were evident, with LMS users possessing better technical skills and problem-solving abilities, whereas non-users required more training and access to resources. Similarly, LMS users demonstrated higher Ability, effectively applying knowledge in practice, whereas non-users struggled due to insufficient practical experience and mentorship. Lastly, in the Reinforcement stage, LMS users benefited from ongoing recognition and support, while non-users lacked sufficient reinforcement mechanisms. The study concludes that targeted interventions, such as personalized training, mentorship, and effective communication, are essential to bridge these gaps and ensure broader LMS adoption across the institution.